ANALYSIS OF THE COMPARISON OF BRAND EQUITY BETWEEN FLEXI PRODUCT AND ESIA PRODUCT IN BOGOR - Indah Kusuma Hayati; Angga Aditya (STIE Binaniaga, 2016)
Globalization era has been insisting on the companies to be able to compete more intense to keep the existence of their companies within the economy of Indonesia refers to telecommunication business. Brand equity is the most important asset for the company to keep up the market. There are 6 CDMA operators in Indonesia, two of them are Telkom with Flexi product and Bakrie with Esia product. Both are very competitive in CDMA network which is they have more than 10 million customers. This research aims to discover the brands equity between Flexi and Esia in Bogor. The elements of brand equity refer to brand awareness, brand association, perceived quality and brand loyalty. Research method is quantitative descriptive which is 100 respondents. Research analysis has applied the Importance Performance Analysis and Cohran test. The result of the research has been indicating that Esia brand equity is stronger than Flexi. The analysis of customers brand equity has been explaining that the customers have not committed yet completely to the product they have been using.Keyword: Brand Equity, Brand Awareness, Brand Association, Perceived Quality and Brand Loyalty